Preparation of high-quality next-generation sequencing libraries from picogram quantities of target DNA - Parkinson, Nicholas J.; Maslau, Siarhei; Ferneyhough, Ben; Zhang, Gang; Gregory, Lorna; Buck, David; Ragoussis, Jiannis; Ponting, Chris P.; Fischer, Michael D. (Genome Research, 2012)
New sequencing technologies can address diverse biomedical questions but are limited by a minimum required DNA input of typically 1 μg. We describe how sequencing libraries can be reproducibly created from 20 pg of input DNA using a modified transpososome-mediated fragmentation technique. Resulting libraries incorporate in-line bar-coding, which facilitates sample multiplexes that can be sequenced using Illumina platforms with the manufacturer's sequencing primer. We demonstrate this technique by providing deep coverage sequence of the Escherichia coli K-12 genome that shows equivalent target coverage to a 1-μg input library prepared using standard Illumina methods. Reducing template quantity does, however, increase the proportion of duplicate reads and enriches coverage in low-GC regions. This finding was confirmed with exhaustive resequencing of a mouse library constructed from 20 pg of gDNA input (about seven haploid genomes) resulting in ∼0.4-fold statistical coverage of uniquely mapped fragments. This implies that a near-complete coverage of the mouse genome is obtainable with this approach using 20 genomes as input. Application of this new method now allows genomic studies from low mass samples and routine preparation of sequencing libraries from enrichment procedures.